Impaired Ocular Tracking and Cortical Atrophy in Idiopathic Rapid Eye Movement Sleep Behavior Disorder. Issue 5 (2nd February 2022) - Chen, Jing; Zhou, Liche; Jiang, Chao; Chen, Zhichun; Zhang, Lina; Zhou, Haiyan; Kang, Wenyan; Jiang, Xufeng; Li, Yuanyuan; Luo, Ningdi; Yao, Mengsha; Niu, Mengyue; et al.
ABSTRACT: Background: Idiopathic rapid eye movement sleep behavior disorder (iRBD) is a prodromal stage of synucleinopathies. Patients with synucleinopathies frequently display eye movement abnormalities. However, whether patients with iRBD have eye movement abnormalities remains unknown. Objective: The aim of this study was to assess eye movement abnormalities and related gray matter alterations and explore whether such abnormalities can serve as biomarkers to indicate phenoconversion to synucleinopathies in iRBD. Methods: Forty patients with iRBD with early disease progression and 35 healthy control subjects participated in a 15‐minute ocular‐tracking task that evaluated their control of eye movement abilities. They also underwent clinical assessments for olfactory function, nonmotor symptoms, and autonomic symptoms, all of which are biomarkers to predict phenoconversion to synucleinopathies in iRBD. A subgroup of the participants (20 patients with iRBD and 20 healthy control subjects) also participated in structural magnetic resonance imaging. Results: The ocular‐tracking ability in patients with iRBD was inferior to that of healthy control subjects in two aspects: pursuit initiation and steady‐state tracking. Cortical thinning in the right visual area V4 in patients with iRBD is coupled with impaired pursuit initiation. Furthermore, prolonged pursuit initiation in patients with iRBD exhibits a trend of correlation with olfactory loss, the earliest biomarker that develops prior to other prodromal biomarkers. Conclusions: We found ocular‐tracking abnormalities in patients with iRBD even early in their disease progression that have not been reported before. These abnormalities are coupled with atrophy of brain areas involved in the perception of object motion and might indicate phenoconversion to synucleinopathies in iRBD. © 2022 International Parkinson and Movement Disorder Society